2023
DOI: 10.23958/ijirms/vol08-i01/1606
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Policies and Practices among Selected Middle East Countries: Are We Walking on the Right Path?

Abstract: Background: The Ministry of Health (MOH) is the foremost authority for public health services in the Middle East through a network of primary, secondary and tertiary healthcare centres. In 2017, the healthcare policy was updated for patient safety by the MOH. Human errors have always been a prime topic of debate in complex systems, especially healthcare, due to the adverse consequences leading to cultural blame; this adversely affects the patient safety policy and quality care and also leads to financial strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the Middle East, for example, a study of patient safety policies and practice described regional and national-level activities but did not evaluate the facilitators and barriers to improving patient safety. 9 A systematic review status of patient safety culture in Arab countries based on the findings of the Hospital Survey on Patient Safety Culture (HSPSC) similarly identified a pervasive culture of blame across the region, but the researchers focused on safety culture as only one element related to patient safety. 2 Similarly, Kang et al undertook comparative research on patient safety culture in Southeast Asian countries, which identified 13 studies using the HSPSC survey.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In the Middle East, for example, a study of patient safety policies and practice described regional and national-level activities but did not evaluate the facilitators and barriers to improving patient safety. 9 A systematic review status of patient safety culture in Arab countries based on the findings of the Hospital Survey on Patient Safety Culture (HSPSC) similarly identified a pervasive culture of blame across the region, but the researchers focused on safety culture as only one element related to patient safety. 2 Similarly, Kang et al undertook comparative research on patient safety culture in Southeast Asian countries, which identified 13 studies using the HSPSC survey.…”
Section: What This Study Addsmentioning
confidence: 99%